Estimation of social costs resulting from mobility changes caused by COVID-19 pandemic - Andrzej Brzezinski; Tomasz Dybicz; Karolina Jesionkiewicz-Niedzinska; Piotr Olszewski; Beata Osinska; Piotr Szagała; Łukasz Szymanski (Archives of Civil Engineering, 2024)
The COVD-19 pandemic has changed the mobility patterns of city dwellers worldwide. These changes apply to the number of trips made, their durations and directions as well as transport modes chosen for travelling purposes. In general, although the number of trips decreased, the use of cars increased and that of public transport declined. These mobility changes were induced by the fear of travelling in crowded vehicles and the extent of restrictions introduced by the governments. The effects of such changes are hard to assess and their evaluation is a complex issue. Based on data available about the transportation system in Warsaw and analysis of Big Data (comprising SIM card movements, acquired from mobile phone network operators), a research project has been carried out under the “IDUB against COVID-19” programme. Transportation models had been built which enabled estimation of the number of trips made at each stage of the pandemic in the spring 2020 and identification of differences through comparison with the models developed for the pre-pandemic conditions (year 2019). The calculations enabled assessment of the social costs of the pandemic associated with the urban transportation system, brought about mostly by changes in using private and public transport modes. The cost efficiency of public transport decreased as a result of limits on the number of passengers per vehicle introduced by transport authorities.